Crystallization and preliminary X-ray diffraction analysis of the interleukin-3 alpha receptor bound to the Fab fragment of antibody CSL362 - Broughton, Sophie E. (International Union of Crystallography, 2014)
Interleukin-3 (IL-3) is a member of the beta common family of cytokines that regulate multiple functions of myeloid cells. The IL-3 receptor-specific alpha subunit (IL3Rα) is overexpressed on stem cells/progenitor cells of patients with acute myeloid leukaemia, where elevated receptor expression correlates clinically with a reduced patient survival rate. The monoclonal antibody (MAb) CSL362 is a humanized MAb derived from the murine MAb 7G3, originally identified for its ability to specifically recognize the human IL-3 receptor and for blocking the signalling of IL-3 in myeloid and endothelial cells. In order to elucidate the molecular mechanism of CSL362 antagonism, a preliminary structure of human IL3Rα in complex with the MAb CSL362 has been determined.